C# 6 fundamentals. (LiveLessons., 2015)
"C# 6 Fundamentals LiveLessons Part I: Introduction is the new C# video from expert trainer Paul Deitel. This video is an introduction to developing applications in the C# 6 programming language. You begin by exploring the Visual Studio IDE. Then you learn about core C# constructs, including classes and objects. You move on to explore program control, and end with a deep exploration of methods in C#."--Resource description page.